2013
DOI: 10.1111/tme.12086
|View full text |Cite
|
Sign up to set email alerts
|

Baseline extracellular potassium level as an indicator of the rate of increase of the same on further storage in CPDA‐1 whole blood units: a potential approach to complement FIFO system for prioritisation of blood bags for release from blood‐banks

Abstract: For CPDA-1 blood bags (i) low baseline potassium blood bags might be preferred for transfusion in cases demanding a low potassium load and (ii) coordinating the ‘first-in-first-out’ (FIFO) policy with ‘early release of blood-bags with high initial potassium’ might be helpful in improving the release of suitable blood units from blood-banks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The supernatant potassium concentration increased immediately after irradiation and was significantly higher than controls after only 2 h. The increase in supernatant potassium in irradiated RCCs was linear over the first 24 h of storage ( R 2 = 0·998 for paediatric and R 2 = 0·996 for full‐size RCCs). Other studies have also reported a time‐dependent correlation with increasing potassium concentrations . The results from this study demonstrate that the increase in supernatant potassium following irradiation between the full‐size and paediatric packs was equivalent, suggesting that red cell membrane damage was not elevated in the smaller packs.…”
Section: Discussionsupporting
confidence: 61%
“…The supernatant potassium concentration increased immediately after irradiation and was significantly higher than controls after only 2 h. The increase in supernatant potassium in irradiated RCCs was linear over the first 24 h of storage ( R 2 = 0·998 for paediatric and R 2 = 0·996 for full‐size RCCs). Other studies have also reported a time‐dependent correlation with increasing potassium concentrations . The results from this study demonstrate that the increase in supernatant potassium following irradiation between the full‐size and paediatric packs was equivalent, suggesting that red cell membrane damage was not elevated in the smaller packs.…”
Section: Discussionsupporting
confidence: 61%
“…In a recent study conducted in a Tertiary care hospital in Uttar Pradesh by Baliar S. and Jaiswal M., who studied CPDA-1 blood bags over a period of 28 days the following conclusions were drawn (i) low baseline potassium blood bags might be preferred for transfusion in cases demanding a low potassium load and (ii) coordinating the 'first-in-first-out' (FIFO) policy with 'early release of blood-bags with high initial potassium' might be helpful in improving the release of suitable blood units from blood-banks. 34 The association between transfusion of stored blood units having high K levels and cardiac dysfunction has been well demonstrated 18,19,35 . We attempt to study possible relationships between K concentrations and levels of some commonly used laboratory parameters in CPDA-1 blood bags and SAGM bags by serially examining them.…”
Section: E) Arrival Of the "Omics Generation"mentioning
confidence: 99%
“…The response of WBCs from transfusion recipients with co-existing morbidities that modulate their immune and/or coagulation or vascular systems is not known and adds further dimensions to the complexity of the potential effects of Transfusion Related Immunomodulation. [34][35][36] Hemolysis during processing can occur due to various reasons. Delay between collection and processing, rapid anticoagulation, high centrifugation speed, rapid addition of additive solution to packed red cells and variation in the quality of blood storage bags all contribute to hemolysis.…”
Section: E) Arrival Of the "Omics Generation"mentioning
confidence: 99%
“…The extracellular K + level increases with the duration of red blood cell (RBC) storage . Furthermore, the K + level in the supernatant of stored packed RBCs increases rapidly and exceeds 50 mEq/L within 1 week after irradiation .…”
mentioning
confidence: 99%